1997
DOI: 10.1103/physrevb.56.3447
|View full text |Cite
|
Sign up to set email alerts
|

Magnetoplasmons in two-dimensional circular sheets of4He+ions

Abstract: We report the results of recent experiments on magnetoplasma modes in circular sheets of 4 He ϩ ions trapped below the surface of superfluid helium at a low temperature. The modes we observe include bulk modes, conventional edge modes, multipole edge modes, and extra satellites of unknown origin. The results are compared with earlier observations of bulk and conventional edge modes. Theories of the modes are reviewed and extended, and a detailed comparison with experiment is carried out.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…There is a suggestion that in the EMP resonance experiment of 2D 4 He + ion pool trapped below a liquid-helium surface [25,26], the observed "extra satellites of unknown origin" may be the ω + mode [24]. In this respect, there is an argument about whether or not the BDW-EMP coupled mode with incompressible motion exists in classical 2D Coulomb systems.…”
Section: Discussion On Incompressible Motionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is a suggestion that in the EMP resonance experiment of 2D 4 He + ion pool trapped below a liquid-helium surface [25,26], the observed "extra satellites of unknown origin" may be the ω + mode [24]. In this respect, there is an argument about whether or not the BDW-EMP coupled mode with incompressible motion exists in classical 2D Coulomb systems.…”
Section: Discussion On Incompressible Motionmentioning
confidence: 99%
“…+ ω Against this suggestion, an argument was presented [26,27] based on an analysis comparing the amplitudes of electric field perturbation arising from boundary displacement and electron density compression. However, this analysis is questionable [24] in terms of the treatment of electron pressure.…”
Section: Discussion On Incompressible Motionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the MP picture to hold we need a characteristic length scale which is independent of the geometrical definition of the mesa and which is short enough to cause a plasmon frequency in the THz regime. As reported by Elliott et al 26 edge-induced magneto plasmon resonance (EIMP) can be observed in measurements on a circular sheet of 4 He + ions, where the resonance frequency is determined by the depletion length of the electron density profile at the sample edge. The depletion length of the carrier density of our GaAs/AlGaAs heterostructure is given by 27…”
Section: Resultsmentioning
confidence: 70%
“…after which ω ac decreases approximately as 1/H. AEMP -excitations were discovered [3,4] in a disk of surface ions in liquid helium exactly at the stage of their frequency going through the maximum as a function of magnetic field H which substantially simplified their identification. Various attempts (listed in the recent published studies [5][6][7] on the ω ac problem) to perform similar experiments in degenerate electron systems have not yet been successful.…”
Section: Introductionmentioning
confidence: 99%